Single-cell RNA sequencing technology was employed to construct a risk prediction model for genes associated with pyroptosis and ferroptosis in lung adenocarcinoma - Longfei Ji; Binyu Wang; Danfei Shi; Weiyun Shen; Xinmin Li; Yong Li (Respiratory Research)
Abstract Background Lung adenocarcinoma (LUAD) is one of the most common subtypes of non-small cell lung cancer, and its mortality rate remains high. As a programmed cell death mode closely related to inflammation, pyroptosis has been found to play an important regulatory role in the tumor immune microenvironment and tumor progression in recent years. However, the characteristics and prognostic value of apoptosis in different cell types in LUAD have not been systematically elucidated. Method This study integrated single-cell RNA sequencing (scRNA seq), bulk transcriptome data, and clinical information to comprehensively analyze the expression patterns and functional roles of pyroptosis related genes (PRGs) in LUAD. We conducted high-resolution clustering analysis on the GSE189357 single-cell dataset, constructed a protein interaction network, and established a prognostic model in conjunction with iron death related genes. Experimental validation of key genes through RNA sequencing and qPCR. Result This study identified 17 different cell types, among which the pyroptosis activity of myeloid dendritic cells and neutrophils was significantly increased. Differentially expressed PRGs are enriched in immune related pathways, such as inflammasome assembly and NOD like receptor signaling pathways. The seven gene prognostic model we constructed (CXCL2, SLC7A5, CAV1, IFNG, EPAS1, TNFAIP3, CYBB) can effectively distinguish high-risk LUAD patients. Functional enrichment analysis revealed that the IL-17 signaling pathway is active in high-risk populations, suggesting that apoptosis may promote the progression of LUAD through immune dysfunction. Immune infiltration and pseudo time trajectory analysis further reveal the close correlation between PRGs expression and the dynamic state of immune cells. RNA sequencing and qPCR confirmed the differential expression of core genes in tumor tissues. Conclusion This study developed a single-cell atlas of pyroptosis in LUAD and identified prognostic biomarkers with potential translational value. Our findings reveal the interaction mechanism between pyroptosis, ferroptosis, and tumor immunity, providing new ideas and targets for precise treatment of LUAD.